Cutaneous CD8+ Cytotoxic T-Cell Lymphoma Infiltrates: Clinicopathological Correlation and Outcome of 35 Cases. Issue 2 (December 2016) - Wobser, Marion; Reinartz, Theresa; Roth, Sabine; Goebeler, Matthias; Rosenwald, Andreas; Geissinger, Eva
Abstract Introduction Cytotoxic CD8+ T-cell lymphomas are only rarely encountered and thus remain only poorly characterized. Our aim was to collect and correlate clinical and histological data of CD8+ skin lymphoma infiltrates to obtain a proper subtype assignment of CD8+ skin lymphoma infiltrates and to derive putative prognostic markers thereof. Methods Formalin-fixed and paraffin-embedded (FFPE) tissue of 35 patients with CD8+ cytotoxic cutaneous T-cell lymphoma infiltrates was retrieved from the archives of the Institute of Pathology and the Department of Dermatology, University Hospital Wuerzburg, dating back from 1998 until 2015. Cytological, histological, immunohistochemical and molecular genetic features were assessed and correlated with respective clinical data. Results The identified cases of CD8+ cytotoxic atypical lymphoproliferative infiltrates of the skin (n = 35) comprised 13 cases of mycosis fungoides (MF)/Sézary syndrome (SS), 4 cases of subcutaneous panniculitis-like T-cell lymphoma (SPTCL), 5 cases of primary cutaneous acral CD8+ lymphoma [formerly indolent CD8+ lymphoid proliferation (ILP)] and 1 case of aggressive epidermotropic primary cutaneous T-cell lymphoma (AECTCL). Moreover, nine cases were classified as primary cutaneous peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS) and three cases as systemic PTCL-NOS. Multiple skin lesions, a high proliferative index and especially a final subtype attribution to AECTCL or systemic PTCL-NOS were associated with a worse survival. Coexpression of CD68 by tumor cells was exclusively observed in indolent acral CD8+ T-cell lymphoma and thus indicated an invariably benign clinical course. No further distinctive markers could be derived from our analysis. Conclusion Cutaneous infiltrates of CD8+ cytotoxic T-cell lymphoma comprise clinically and histologically heterogeneous entities of either primary cutaneous T-cell lymphomas or secondary infiltrates of otherwise systemic peripheral T-cell lymphomas. A thorough clinicopathological correlation with respective staging examinations remains the mainstay for correct subtype assignment and proper prognostication as long as no better markers have been defined.